Low-profile double plating versus conventional single plating in midshaft clavicle fractures: A retrospective study and initial experience with this novel technique - Yannic Lecoultre; Bryan van de Wall; Bjoern-Christian Link; Charlotte Kik; Reto Babst; Frank Beeres (PLoS ONE, 2025)
Background Low-profile double plating seems a viable alternative to conventional single plating for fixation of midshaft clavicle fractures. This study aims to compare the two techniques regarding healing, complications, and removal rate. Methods This retrospective cohort study included all patients >16 years that underwent plate fixation for midshaft clavicle fractures between 2020 and 2022 at one trauma-center. Exclusion criteria encompassed pathological or open fractures, refractures and delayed presentation or treatment more than 14 days after the accident. Patients were categorized into two treatment groups: Single plating (Synthes 3.5mm LCP superior / anterior or Synthes 2.7mm VA-LCP superior) and low-profile double plating (2.0 superior combined with either 2.4 or 2.7mm anterior mini-plate). Treatment groups were compared regarding healing, complications, and removal rate. Results A total of 99 patients were included: 74 in the single plating and 25 in the double plating group. Implant failures within the first three months were comparable in both groups (4.0% double plating versus 2.7% single, p = 0.744, of which one was caused by infection). Low-profile double plating had a significantly lower operation duration (95 versus 111 minutes, p = 0.019). Long-term follow-up data was available in 60 patients in the single plating and 20 in the double plating group. The need for reintervention was significantly lower in the double plating group (n = 5, 25.0% vs. n = 31, 51.7%, p = 0.038). These reinterventions were predominantly caused by implant irritation in both groups (n = 4, 20% double plating versus n = 29, 48.3% single plating, p = 0.026). All fractures healed in both groups. Conclusion Low-profile double plating attains comparable healing rates as single plating and has a significantly lower risk for re-intervention as well as a shorter operation duration. The lower reintervention rate is mainly explained by a lower incidence of implant irritation in the double plating group.